The outcome of Radial Neck Fracture Treated with Closed/ Open Reduction and Retrograde Kirschner Wires Fixation in the Paediatric Age Group - Sapkota, K.; Ranjeet, N.; Onta, P. R.; Thapa, P. (Kathmandu University Medical Journal, 2022)
Background Radial neck fractures in children are rare injuries, representing 1 to 5% of all elbow pediatric fractures. Most of them are non-displaced or slightly displaced and treated conservatively. Severely displaced or angulated radial neck fractures (Judet type III and IV fractures or O’Brien type III radial neck fractures) requires surgical treatment. Objective To study the clinical and radiological outcomes of fractures following closed or open reduction and percutaneous intramedullary stabilization of the displaced radial neck fracture in children. Method There were 24 children with displaced radial neck fracture Judet type II, III and IV fractures O’Brien type II, III who underwent closed reduction and retrograde intramedullary stabilization with Kirschner wires. Functional outcomes were evaluated based on of Mayo Elbow Performance Score. Result The mean age of patients was 8.42 ± 1.82 years with boys 15(62.5%) and girls 9(37.5%) in number. An excellent result was seen in 5(20.8%) cases and good results in 15(62.5%) cases according to the Mayo elbow performance score. Analyzing a passive and active range of motion, 5 had excellent results, 15 had good results and 4 had fair results compared to the normal side. Radiological evaluation showed fracture healing in excellent or good alignment according to Ursei radiological evaluation classification. Conclusion Closed reduction and retrograde intramedullary Kirschner wires stabilization for the displaced radial neck fracture provide excellent clinical and radiological results with few complications.